Experience in information management and control of electric and magnetic fields of electrical companies - Arnera, Patricia Liliana (2012)
The use of electricity involves a broad range of activities that cause a wide variety of environmental impacts during the extraction, processing, transport and consuming procedures, due to their diversity, characteristics and relative importance. It is the role of the State to elaborate the guidelines and regulations for the environmental aspects in the different segments of the market, for different electrical energy sources and in all the stages of the process, from the initial evaluation to the construction and exploitation phases. On the other hand, the State should exercise the Controller’s role in order to guarantee the adequate environmental management. The State is also faced with the complexity of the negotiations with multiple key players – public, private, national and international- who decide the course of action and the contents of the environmental management. Among the environmental key aspects to be considerate, there are the electric and magnetic fields, in which society has taken special interest as they are believed to be involved in health hazard. Some of the faculties of the National Electricity Regulator (Ente Nacional Regulador de la Electricidad - ENRE) include the issuing of regulations and technical procedures to be fulfilled by the agents, and to verify their compliance. The ENRE has gathered information regarding electric and magnetic fields that includes those planned by the private environmental planning departments and those obtained ex-post in the role of controller. In order to systematize this information, a database has been designed considering different types of electric facilities, the company which they belong to, equipment used in the measurements, representative layouts with measure points and the profiles of electric and magnetic fields that were obtained. This database results in a management tool for evaluation of the evolution and control of the environmental parameters and in an instrument for communication purposes.